Primary mediastinal hydatidosis successfully treated with combined medical therapy and VATS (Video-assisted thoracoscopic surgery) - Almurtada Razok (12204854) (2021)
Mediastinal involvement of hydatidosis is rare even in endemic areas. Isolated mediastinal without lung or liver involvement is even less commonly reported. We present the case of a young gentleman who was diagnosed with primary mediastinal hydatidosis based on clinical, radiological and pathological criteria. He underwent successful resection of the lesion by VATS (Video-assisted thoracoscopic surgery) preceded by two weeks of medical treatment with albendazole and had an excellent outcome. To the best of our knowledge, this is the first reported case in the state of Qatar. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e01008